An Insight to People’s Aesthetic Responses to Their Returned Environment - Sarı, Canan Pembe (Eastern Mediterranean University (EMU), 2012)
ABSTRACT: This thesis is primarily concerned with aesthetic issues of symbolic expressions and preferences that are reflected in housing designs. The study consists of two major parts: First, features the process of reviewing existing literature on the various influential topics related to the field of housing and aesthetics such as formal and symbolic responses of the users. These responses occur as a part of the architectural language inflicted upon designs of housing in this study’s four selected regions in the Yeni Boğaziçi area, Gazimağusa, North Cyprus. The existing literature includes works from both architectural developments and environmental design issues, focusing mainly on the social and symbolical developments of housing and ideas of how a house becomes a ‘home’. The second part to the study relates to the analysis of housing developments constructed during the recent years by the specific user profile of this study. Focusing on this unique user group, being British Cypriots that have returned to Northern Cyprus after living in England, UK for several years, provided the opportunity to gain an insight related to their aesthetic responses to their returned environments through housing. The main objective of the study was to determine general characteristics of this user group’s aesthetic preferences and what role their past environment played in their returned environment. Three different field surveys were carried out for the objectives of the study: Site inspections, semi-structured questionnaires and structured interviews. The surveys were carried out in four different sample areas situated in close proximity along the out skirts of the currently-developing region of Yeni Boğaziçi region. The findings of the study, in general suggest that not only the physical elements, but symbolic elements which are coming from one’s past environment or life style, plays significant role through the process of turning a house into a “home”. Keywords: Housing, symbolism, aesthetic response, past and returned environments. …………………………………………………………………………………………………………………………………………………………………………………………………………………… ÖZ: Bu tezin öncelikli olarak ilgilendiği konu, konut tasarımlarında yansıtılan sembolik ifadeler ve tercihlerde ortaya çıkan estetik sorunlardır. Bu çalışma iki ana bölümden meydana gelmektedir: Birinci bölüm içeriği, konut tasarımı ve estetik kuramında etkili olan konularla, kullanıcıların biçimsel ve sembolik tepkileri gibi, konuyla ilgili mevcut literatürün incelenmesinden oluşmaktadır. Belirli bir kullanıcı grubunun, ne tür biçimsel ve/veya sembolik tepkiler verdiği, bu çalışma içi Kuzey Kıbrıs’ın Yeniboğaziçi köyünde seçilen dört bölgede bulunan konut tasarımları üzerinden okunmaya çalışılmıştır. İncelenen literatür ve kaynaklar, konut yapımında sosyal ve sembolik gelişmeler ve bir evin nasıl bir ‘yuva’ya dönüştüğüyle ilgili fikirler üzerine yoğunlaşarak, hem mimari gelişim hem de çevresel gelişim konularından farklı çalışmalara değinmektedir. Çalışmanın ikinci bölümü ise bu çalışma için belirlenen kullanıcı profili tarafından son yıllarda inşaa edilen konutların analizi ile ilgilidir. Birkaç yıl İngiltere, Birleşik Krallık’ta yaşadıktan sonra tekrar Kıbrıs’a dönen Kıbrıslı İngilizlerden oluşan bu kendine özgü kullanıcı grubu üzerine yoğunlaşmak onların yerleşim sürecinde geri döndükleri çevreye gösterdikleri estetik tepkilerini anlama fırsatını sağlamıştır. Çalışmanın temel amacı; kullanıcı grubunun estetik tercihlerinin yanısıra geçmişteki çevrelerinin geri döndükleri çevreye karşı mimari dışavurumlarının genel özelliklerini belirlemektir. Çalışmanın amacına ulaşmak adına üç farklı alan çalışması gerçekleştirilmiştir: yerinde inceleme çalışması, yarı-yapılandırılmış anketler ve yapılandırılmış mülakatlar. Araştırmalar Yeniboğaziçi köyünün gelişmekte olan bölgelerinin dış mahallelerine yakın mesafede konuşlandırılmış dört farklı örnek alanda gerçekleştirilmiştir. Bu çalışmanın bulguları genel anlamda sadece fiziksel unsurların değil, kişinin geçmiş çevresinden yada yaşam tarzından gelen sembolik unsurların da bir evin ‘yuva’ya dönüşmesinde önemli bir rolü olduğunu ileri sürmektedir. Anahtar kelimeler: Konut çalışmaları, sembolizm, estetik tepki, geçmiş ve geri dönülen çevreler.
Master of Science in Architecture. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Architecture, Dept. of Architecture, 2012. Supervisor: Assist. Prof. Dr. Ceren Boğaç.
Keywords: Architecture; Housing Design - Aesthetic - Cyprus, North; Housing - Symbolism - Aesthetic Response - Past and Returned Environments